High-capacity positive electrode material precursor and preparation method thereof, lithium ion battery positive electrode material, lithium ion battery and lithium battery equipment

Through the design of the nickel-cobalt-manganese ternary precursor, the number of wafers and particle structure of (101) are controlled, and the problems of the cathode material capacity and cycling performance of lithium-ion batteries are solved, and a lithium-ion battery with high capacity and excellent electrical performance are achieved.

CN119230813APending Publication Date: 2024-12-31HUNAN ZOOMWE NEW ENERGY TECH CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310805092.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

While the existing lithium-ion battery positive electrode materials increase capacity, it is difficult to maintain the battery's cycling performance, and the lithium-ion transmission path is too long or the deintercalation speed is too slow, affecting the overall performance of the battery.

Method used

Using a nickel-cobalt-manganese ternary precursor, the particle diameter is controlled by controlling the number of wafers in the range of 45≤N≤80, combining spindle-shaped primary particles and radially arranged secondary particles, and the co-precipitation reaction method is used to control the particle diameter. and chemical formulas to optimize lithium ion transport paths.

Benefits of technology

It realizes the high capacity and excellent electrical performance of lithium-ion batteries, ensures that the lithium-ion transmission path is short and the deintercalation speed is appropriate, and improves the overall capacity and cycling performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230813A_ABST
    Figure CN119230813A_ABST
Patent Text Reader

Abstract

The invention provides a high-capacity positive electrode material precursor, which comprises a secondary particle formed by a plurality of primary particles, and the number N of (101) wafers of the positive electrode material precursor satisfies: 45 < = N < = 80; wherein N = D / d, D is the crystal grain size of the crystal face (101), and d is the interplanar spacing of the crystal face (101). The invention also provides a preparation method of the high-capacity positive electrode material precursor, which comprises the following steps: adding a corresponding metal salt solution, a complexing agent and a precipitator into a base solution under the protection of inert gas, and carrying out coprecipitation reaction to obtain the high-capacity positive electrode material precursor, in the coprecipitation reaction process, part of liquid of a reaction system is continuously discharged or solid-liquid mixed slurry is continuously discharged in an overflow manner. According to the high-capacity positive electrode material precursor provided by the invention, by controlling the (101) wafer number of the primary particles, the high-capacity positive electrode material precursor has high capacity, the lithium ion transmission rate on a crystal structure is regulated and controlled, and the material capacity exertion is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium-ion batteries, and in particular to a high-capacity positive electrode material precursor and a preparation method thereof, a lithium-ion battery positive electrode material, a lithium-ion battery and a lithium-ion battery device. Background Art

[0002] With the rapid rise of the global new energy industry, lithium-ion batteries as new energy vehicle batteries have received widespread attention. Ternary cathode materials have many advantages such as high capacity, high energy density, and good cycle performance. Cathode materials account for a large part of the cost of lithium-ion batteries and largely determine the electrical performance of the battery. Research on ternary cathode materials has become one of the research hotspots in the field of lithium-ion batteries.

[0003] Currently, major battery manufacturers and car companies are pursuing larger capacity batteries. How to increase capacity without sacrificing battery cycle performance is the focus of research. Summary of the invention

[0004] The purpose of the present application is to provide a high-capacity nickel-cobalt-manganese ternary precursor and a preparation method thereof, a lithium-ion battery positive electrode material, a lithium-ion battery and a lithium battery device to solve the above-mentioned problems.

[0005] To achieve the above objectives, this application adopts the following technical solutions:

[0006] A high-capacity positive electrode material precursor, the positive electrode material precursor comprising secondary particles formed by a plurality of primary particles, the number N of (101) chips of the positive electrode material precursor satisfying: 45≤N≤80; wherein N=D / d, D is the grain size of the (101) crystal plane, and d is the (101) crystal plane spacing; preferably, the number N of (101) chips of the positive electrode material precursor satisfying: 50≤N≤75.

[0007] Preferably, the average particle size D50 of the positive electrode material precursor is 1-15 μm, and the particle size distribution is 0.5<span<1.7.

[0008] Preferably, the cathode material precursor comprises a plurality of spindle-shaped primary particles, and the cathode material precursor satisfies one or more of the following conditions:

[0009] a. The average width of the primary particles is 30-120nm and the average length is 200-1200nm;

[0010] b. The average aspect ratio of the primary particles is 4-25, preferably 4-15.

[0011] Preferably, the primary particles located on the outer layer of the secondary particles of the positive electrode material precursor are arranged radially.

[0012] Preferably, the cathode material precursor satisfies one or more of the following conditions:

[0013] The chemical formula of the positive electrode material precursor is Ni x Co y Mn z M w (OH) 2 , wherein x+y+z+w=1, 0.5≤x<1, 0≤y≤0.5, 0≤z≤0.5, 0≤w≤0.01, and M is selected from at least one of Ti, Mg, Zn, Cu, Al, Ga, In, F, La, Cr, Si, Sn, W, Mo, Y, Nb, Ca, Sm, V, Hf, Zr, Fe or B;

[0014] The chemical formula of the positive electrode material precursor is Ni x Co y Mn z M w (OH) 2 , where x+y+z+w=1, 0.9≤x<1, 0≤y≤0.1, 0≤z≤0.1, 0.001≤w≤0.01, M is Al or W;

[0015] The average particle size D50 of the positive electrode material precursor is 9-12 μm, and the particle size distribution is 1≤span<1.5;

[0016] The average particle size D50 of the positive electrode material precursor is 1.5-5 μm, and the particle size distribution is 0.5<span<1;

[0017] The average particle size D50 of the secondary particles of the positive electrode material precursor is 9-12 μm, and the particle size distribution span is 0.5<span<1.

[0018] The present application also provides a method for preparing a high-capacity cathode material precursor, comprising:

[0019] Under the protection of inert gas, a metal salt solution, a complexing agent and a precipitant are added to the base liquid to perform a coprecipitation reaction to obtain the high-capacity positive electrode material precursor; during the coprecipitation reaction, part of the liquid in the reaction system is continuously discharged or the solid-liquid mixed slurry is continuously discharged by overflow.

[0020] Preferably, the preparation method satisfies one or more of the following conditions:

[0021] a. The concentration of the metal salt solution is 1.0-2.0 mol / L, and the solute in the metal salt solution is one or more of soluble nitrates, chlorides and sulfates of metals;

[0022] The concentration of the metal salt solution refers to the concentration of total metal ions in the metal salt solution.

[0023] b. The pH of the base solution is 9.5-12.0;

[0024] c. The coprecipitation reaction process is controlled as follows: the temperature is 40-80°C, the pH is 9.5-11.7, and the ammonia concentration is 1-5g / L;

[0025] d. The coprecipitation reaction further comprises stirring, and the stirring speed is 100-200r / min;

[0026] e. the precipitating agent comprises an aqueous solution of sodium hydroxide, and the complexing agent comprises aqueous ammonia;

[0027] f. During the coprecipitation reaction, the flow rate of the precipitant is 0.74-9.25% / h of the available volume of the reaction vessel, and the flow rate of the metal salt solution is 2-25% / h of the available volume of the reaction vessel;

[0028] g. After the coprecipitation reaction is completed, the steps include solid-liquid separation, solid drying and screening.

[0029] The present application also provides a lithium-ion battery positive electrode material, the raw material of the lithium-ion battery positive electrode material includes the high-capacity positive electrode material precursor.

[0030] The present application also provides a lithium-ion battery, which includes the lithium-ion battery positive electrode material.

[0031] The present application also provides a lithium battery device, comprising the lithium-ion battery.

[0032] Compared with the prior art, the beneficial effects of this application include:

[0033] The high-capacity positive electrode material precursor provided in the present application analyzes the number of (101) chips of the positive electrode material precursor and finds that when the number of (101) chips of the positive electrode material precursor is within an appropriate range (45-80 layers), the lithium battery prepared from the corresponding positive electrode material can obtain a higher capacity. Specifically, lithium ions tend to be transported within the (001) crystal plane of the precursor (the (001) crystal plane of the ternary precursor is transformed into the (003) plane after sintering). After the lithium ions are transported to the (001) crystal plane boundary, they are transported to the next (001) crystal plane through the (101) crystal plane or deintercalated into the electrolyte. When the number of (101) crystal chips is small, it can ensure that the path for lithium ion transmission within the (001) plane is not too long and the deintercalation speed of lithium ions on the (101) plane is guaranteed. When the number of (101) crystal chips is very small, the crystal tends to grow on the (001) crystal plane, resulting in the corresponding (001) crystal plane being too large in size, the lithium ion transmission path becoming longer or the deintercalation speed becoming slower, which is not conducive to the capacity performance of lithium batteries prepared with corresponding positive electrode materials.

[0034] The method for preparing a high-capacity positive electrode material precursor provided in the present application adopts an intermittent or continuous production method to prepare the above-mentioned positive electrode material precursor having a (101) wafer number within a suitable range through a solution co-precipitation reaction.

[0035] The lithium-ion battery positive electrode material, lithium-ion battery and lithium battery equipment provided in the present application have a large positive electrode initial charge and discharge capacity, excellent electrical performance and good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0037] Figure 1 This is a SEM image of the cathode material precursor obtained in Example 1;

[0038] Figure 2 This is the XRD pattern of the cathode material precursor obtained in Example 1;

[0039] Figure 3 This is a SEM image of the cathode material precursor obtained in Example 2;

[0040] Figure 4 CP diagram of the cathode material precursor obtained in Example 2;

[0041] Figure 5 This is the XRD pattern of the cathode material precursor obtained in Example 2;

[0042] Figure 6This is a SEM image of the cathode material precursor obtained in Example 3;

[0043] Figure 7 This is the XRD pattern of the cathode material precursor obtained in Example 3;

[0044] Figure 8 This is a SEM image of the cathode material precursor obtained in Example 4;

[0045] Fig. 9 This is the XRD pattern of the cathode material precursor obtained in Example 4;

[0046] Fig.10 This is a SEM image of the cathode material precursor obtained in Example 5;

[0047] Fig.11 This is the XRD pattern of the cathode material precursor obtained in Example 5;

[0048] Fig.12 This is a SEM image of the cathode material precursor obtained in Example 6;

[0049] Fig.13 This is the XRD pattern of the positive electrode material precursor obtained in Example 6;

[0050] Fig.14 This is a SEM image of the positive electrode material precursor obtained in Comparative Example 1;

[0051] Fig.15 This is the XRD pattern of the positive electrode material precursor obtained in Comparative Example 1;

[0052] Fig.16 This is a SEM image of the positive electrode material precursor obtained in Comparative Example 2;

[0053] Fig.17 This is the XRD diagram of the positive electrode material precursor obtained in Comparative Example 2. DETAILED DESCRIPTION

[0054] As used herein:

[0055] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0056] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0057] When an amount, concentration, or other value or data is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0058] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0059] A high-capacity positive electrode material precursor, the positive electrode material precursor includes secondary particles formed by multiple primary particles, and the number N of (101) crystal chips of the positive electrode material precursor satisfies: 45≤N≤80; wherein N=D / d, D is the (101) crystal plane grain size, and d is the (101) crystal plane spacing.

[0060] (101) The calculation of the number of wafers involves the following formula:

[0061] Formula (1) Scherrer formula: D = kλ / βcosθ;

[0062] Formula (2) Bragg formula: d = nλ / 2sinθ;

[0063] Formula (3): (101) chip number N = D / d, where D is the grain size of the (101) crystal plane (nm), d is the (101) crystal plane spacing (nm), k is the Scherrer constant, n is 1, λ is the wavelength of the incident X-ray (nm), β is the half-peak width corresponding to the (101) crystal plane, and θ is the diffraction angle corresponding to the (101) crystal plane.

[0064] The transmission path and deintercalation speed of lithium ions determine the capacity of the material. Lithium ions tend to be transmitted within the (001) crystal plane, and are transmitted or deintercalated through the (101) crystal plane. When the number of (101) crystals is small, the transmission path is short, which is conducive to the capacity. However, when the number of (101) crystals is very small, the corresponding (001) crystal plane will grow preferentially, resulting in a longer lithium ion transmission path, which is not conducive to the capacity performance.

[0065] Optionally, the number of (101) crystals of the primary particles constituting the positive electrode material precursor may be 45, 50, 60, 70, 80 or any value between 45 and 80.

[0066] In a preferred embodiment, the number N of (101) wafers of the positive electrode material precursor satisfies: 50≤N≤75.

[0067] In an optional embodiment, the average particle size D50 of the positive electrode material precursor is 1-15 μm, and the particle size distribution is 0.5<span<1.7;

[0068] Optionally, the average particle size D50 of the positive electrode material precursor can be 1 μm, 1.5 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or any value between 1-15 μm, and the particle size distribution span (span = (D90-D10) / D50) can be 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6 or any value greater than 0.5 and less than 1.7.

[0069] In an optional embodiment, the cathode material precursor includes a plurality of spindle-shaped primary particles, and the cathode material precursor satisfies one or more of the following conditions:

[0070] a. The average width of the primary particles is 30-120nm and the average length is 200-1200nm;

[0071] Optionally, the primary particles are spindle-shaped, and the average width may be 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm or any value between 30-120nm; the average length may be 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm or any value between 200-1200nm;

[0072] b. The average aspect ratio of the primary particles is 4-25, and the average aspect ratio of the primary particles can be 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 17, 19, 20, 21, 23, 25 or any value between 4 and 25; the average aspect ratio of the primary particles is within a certain range, which can shorten the movement path of lithium ions inside and outside the primary particles, and is also beneficial to the performance of capacity.

[0073] Preferably, the average aspect ratio of the primary particles is 4-15.

[0074] It should be noted that when the primary particles of the positive electrode material precursor are spindle-shaped, for example, Figure 1 As shown in the figure, the width of the primary particle is selected from the widest distance W in the middle of the spindle-shaped part, and the length of the primary particle is selected from the distance L between the thinnest parts at the two ends; the average length of the primary particle is Figure 1 The average length of multiple primary particles in the sample is Figure 1 The average width of multiple primary particles in the image. The average aspect ratio of primary particles is the ratio of the average length to the average width. In order to make the selected primary particles more representative, the primary particles with more complete morphology and more obvious boundaries in the image are preferably selected for measurement.

[0075] Optionally, the primary particles located in the outer layer of the secondary particles of the positive electrode material precursor are arranged radially. When the primary particles are arranged radially, the movement path of lithium ions inside the secondary particles becomes shorter, thereby improving the mobility of lithium ions and facilitating the capacity. It is understood that when the outer layer is a single layer, the secondary particles are arranged radially; when the outer layer is multi-layered, the secondary particles in the outermost layer are arranged radially.

[0076] Optionally, the porosity of the secondary particles of the cathode material precursor is 3-10%. The porosity within the appropriate range can increase the contact area between lithium ions and the electrolyte while maintaining the stability of the material, thereby improving the overall capacity. This application uses image analysis software (ImageJ) to directly calculate the pore area and cross-sectional area of ​​each region, and the porosity of different regions is calculated by (porosity = pore area of ​​each region / cross-sectional area of ​​each region × 100%).

[0077] In an optional embodiment, the cathode material precursor satisfies one or more of the following conditions:

[0078] A. The chemical formula of the positive electrode material precursor is Ni x Co y Mn z M w(OH)2, wherein x+y+z+w=1, 0.5≤x<1, 0≤y≤0.5, 0≤z≤0.5, 0≤w≤0.01, and M is selected from at least one of Ti, Mg, Zn, Cu, Al, Ga, In, F, La, Cr, Si, Sn, W, Mo, Y, Nb, Ca, Sm, V, Hf, Zr, Fe or B;

[0079] Optionally, x can be 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84 , 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99 or any value greater than or equal to 0.5 and less than 1; y can be 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26 , 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.5 or any value greater than or equal to 0 and less than or equal to 0.5; z can be 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17 7, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49 or any value greater than or equal to 0 and less than or equal to 0.5. w may be 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, or any value greater than or equal to 0 and less than or equal to 0.01.

[0080] Preferably, the chemical formula of the positive electrode material precursor is Ni x Co y Mn z M w (OH) 2 , where x+y+z=1, 0.9≤x<1, 0<y≤0.1, 0≤z≤0.1, 0.001≤w≤0.01, and M is Al or W.

[0081] B. The average particle size D50 of the secondary particles of the positive electrode material precursor is 9-12 μm, and the particle size distribution span is 1≤span<1.5;

[0082] C. The average particle size D50 of the secondary particles of the positive electrode material precursor is 1.5-5 μm, and the particle size distribution span is 0.5<span<1;

[0083] D. The average particle size D50 of the secondary particles of the positive electrode material precursor is 9-12 μm, and the particle size distribution span is 0.5<span<1.5.

[0084] The present application also provides a method for preparing a high-capacity cathode material precursor, comprising:

[0085] Under the protection of inert gas, a metal salt solution, a complexing agent and a precipitant are added to the base liquid to perform a coprecipitation reaction to obtain the high-capacity positive electrode material precursor; during the coprecipitation reaction, part of the liquid in the reaction system is continuously discharged or the solid-liquid mixed slurry is continuously discharged by overflow.

[0086] It should be noted that, in the preparation method provided in the present application, "continuously discharging part of the liquid in the reaction system during the co-precipitation reaction" refers to an intermittent production method, in which no solid matter is discharged, but only the liquid in the reaction system is continuously discharged (usually a concentrator is used for discharge); "continuously discharging the solid-liquid mixed slurry by overflow" refers to a continuous production method, in which the solid-liquid mixture is continuously discharged during the reaction.

[0087] In addition, whether it is intermittent or continuous, a method of preparing seed crystals first and then preparing the precursor can be adopted, or a method of directly reacting to obtain the precursor without preparing seed crystals can be adopted. The application does not limit this.

[0088] In an optional embodiment, the preparation method satisfies one or more of the following conditions:

[0089] a. The concentration of the metal salt solution is 1.0-2.0 mol / L, and the solute in the metal salt solution is one or more of soluble nitrates, chlorides and sulfates of metals;

[0090] Optionally, the concentration of the metal salt solution may be 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2.0 mol / L or any value between 1.0 and 2.0 mol / L;

[0091] b. The pH of the base solution is 9.5-12.0;

[0092] Optionally, the pH of the base solution may be 9.5, 10.0, 10.5, 11.0, 11.5, 12.0 or any value between 9.5 and 12.0;

[0093] c. The coprecipitation reaction temperature is 40-80°C, the system pH is 9.5-11.7 during the reaction, and the ammonia concentration is 1-5g / L;

[0094] Optionally, the temperature of the coprecipitation reaction can be 40°C, 50°C, 60°C, 70°C, 80°C or any value between 40-80°C, the system pH during the reaction can be 9.5, 9.6, 9.7, 9.9, 10.0, 10.1, 10.2, 10.3, 10.4, 10.5, 10.6, 10.7, 10.8, 10.9, 11.0, 11.1, 11.2, 11.3, 11.4, 11.5, 11.6, 11.7 or any value between 9.5-11.7, and the ammonia concentration can be 1 g / L, 1.5 g / L, 2 g / L, 2.5 g / L, 3 g / L, 3.5 g / L, 4 g / L, 4.5 g / L, 5 g / L or any value between 1-5 g / L;

[0095] d. The coprecipitation reaction further comprises stirring at a speed of 100-200 r / min;

[0096] Optionally, the coprecipitation reaction is carried out under stirring, and the stirring speed may be 100 r / min, 110 r / min, 120 r / min, 130 r / min, 140 r / min, 150 r / min, 160 r / min, 170 r / min, 180 r / min, 190 r / min, 200 r / min or any value between 100-200 r / min;

[0097] e. the precipitating agent comprises an aqueous solution of sodium hydroxide, and the complexing agent comprises aqueous ammonia;

[0098] f. During the coprecipitation reaction, the flow rate of the precipitant is 0.74-9.25% / h of the available volume of the reaction vessel, and the flow rate of the metal salt solution is 2-25% / h of the available volume of the reaction vessel;

[0099] Optionally, during the coprecipitation reaction, the flow rate of the precipitant may be 0.74% / h, 0.9% / h, 1% / h, 2% / h, 3% / h, 4% / h, 5% / h, 6% / h, 7% / h, 8% / h, 9% / h, 9.25% / h or any value between 0.74% / h and 9.25% / h of the available volume of the reaction vessel, and the flow rate of the metal salt solution may be 2% / h of the available volume of the reaction vessel. % / h, 3% / h, 4% / h, 5% / h, 6% / h, 7% / h, 8% / h, 9% / h, 10% / h, 11% / h, 12% / h, 13% / h, 14% / h, 15% / h, 16% / h, 17% / h, 18% / h, 19% / h, 20% / h, 21% / h, 22% / h, 23% / h, 24% / h, 25% / h or any value between 2-25% / h;

[0100] g. After the coprecipitation reaction is completed, the steps include solid-liquid separation, solid drying and screening.

[0101] The present application also provides a lithium-ion battery positive electrode material, the raw materials of which include the high-capacity positive electrode material precursor.

[0102] The present application also provides a lithium-ion battery, comprising the lithium-ion battery positive electrode material.

[0103] The present application also provides a lithium battery device, comprising the lithium-ion battery.

[0104] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0105] Example 1

[0106] This embodiment provides a high-capacity cathode material precursor, and the preparation method thereof is as follows:

[0107] Step 1: Select soluble salts of nickel, cobalt and manganese as raw materials, prepare a 2.0 mol / L nickel-cobalt-manganese mixed solution according to the molar ratio of Ni:Co:Mn=95:4:1, prepare a 32 wt% NaOH aqueous solution, and prepare a 21 wt% ammonia aqueous solution as a complexing agent.

[0108] Step 2: adding a certain amount of pure water, the prepared NaOH aqueous solution and ammonia aqueous solution into a reactor, stirring evenly to obtain a first bottom liquid with a pH of 11.00-11.60; passing an inert gas to protect the first bottom liquid, and using a circulating magnetic pump to uniformly add the nickel-cobalt-manganese mixed solution, the NaOH aqueous solution and the ammonia aqueous solution into the first bottom liquid reactor, maintaining the temperature in the reactor constant, and continuously feeding and discharging. During the reaction, the pH is controlled to fluctuate within the range of 11.50-11.70 and the ammonia concentration is controlled to fluctuate within the range of 4-4.5 g / L by fine-tuning the flow rate of the precipitant and the complexing agent, so as to maintain the particle size stable. After the reaction is stable, the material is ready to be connected, and the slurry is centrifuged to obtain nickel-cobalt-manganese hydroxide seed crystals with an average particle size D50 of 2.5 μm.

[0109] Step 3: putting the nickel-cobalt-manganese hydroxide seed crystals of step 2 into a reactor, adding a certain amount of pure water, the prepared NaOH solution and ammonia solution into the reactor, stirring evenly, and obtaining a second bottom liquid with a pH of 10.50-10.80; passing an inert gas to the second bottom liquid for protection, and uniformly adding the nickel-cobalt-manganese mixed solution, the NaOH solution and the ammonia solution into the second bottom liquid reactor by a circulating magnetic pump, wherein the flow rate of the nickel-cobalt-manganese mixed solution is 8% / h and the flow rate of the NaOH solution is 2.96% / h based on the total capacity of the reactor, the temperature in the reactor is maintained constant, and the material is continuously fed and discharged (discharging the solid-liquid mixed slurry). During the reaction process, the pH is controlled to fluctuate within the range of 10.70-10.80 and the ammonia concentration is controlled to fluctuate within the range of 3.0-3.5 g / L by fine-tuning the flow rate of the precipitant and the complexing agent, and the nickel-cobalt-manganese hydroxide seed crystals of step 2 are continuously added to maintain the stable particle size. After the reaction is stable, the material is prepared to obtain nickel-cobalt-manganese hydroxide.

[0110] Step 4: The reaction product of step 3 is centrifuged and washed, and then dried and sieved to obtain a nickel-cobalt-manganese ternary precursor powder sample 1.

[0111] The SEM and XRD patterns of the precursor are shown in Figure 1 , Figure 2 shown.

[0112] Example 2

[0113] This embodiment provides a high-capacity cathode material precursor, and the preparation method thereof is as follows:

[0114] Step 1: Select soluble salts of nickel, cobalt and manganese as raw materials, prepare a 2.0 mol / L nickel-cobalt-manganese mixed solution according to the molar ratio of Ni:Co:Mn=94:5:1, prepare a 32 wt% NaOH aqueous solution, and prepare a 21 wt% ammonia aqueous solution as a complexing agent.

[0115] Step 2: adding a certain amount of pure water, the prepared NaOH aqueous solution and ammonia aqueous solution into a reactor, stirring evenly to obtain a first bottom liquid with a pH of 11.00-11.60; passing an inert gas to protect the first bottom liquid, and uniformly adding the nickel-cobalt-manganese mixed solution, the NaOH aqueous solution and the ammonia aqueous solution into the first bottom liquid reactor with a circulating magnetic pump, maintaining the temperature in the reactor constant, and continuously feeding and discharging. During the reaction, the pH is controlled to fluctuate within the range of 11.50-11.70 and the ammonia concentration is controlled to fluctuate within the range of 3.0-3.5 g / L by fine-tuning the flow rate of the precipitant and the complexing agent, so as to maintain the particle size stability. After the reaction is stable, the material is ready to be connected, and the slurry is centrifuged to obtain nickel-cobalt-manganese hydroxide seed crystals with an average particle size D50 of 2.5 μm.

[0116] Step 3: putting the nickel-cobalt-manganese hydroxide seed crystals of step 2 into a reactor, adding a certain amount of pure water, the prepared NaOH aqueous solution and ammonia aqueous solution into the reactor, stirring evenly, and obtaining a second bottom liquid with a pH of 10.40-10.60; passing an inert gas to the second bottom liquid for protection, and uniformly adding the nickel-cobalt-manganese mixed solution, the NaOH aqueous solution and the ammonia aqueous solution into the second bottom liquid reactor by a circulating magnetic pump, wherein the flow rate of the NaOH aqueous solution is 5.55% / h and the flow rate of the nickel-cobalt-manganese mixed solution is 15% / h based on the total capacity of the reactor, the temperature in the reactor is maintained constant, and the material is continuously fed and discharged (discharging the solid-liquid mixed slurry). During the reaction process, the pH is controlled to fluctuate within the range of 10.20-10.30 and the ammonia concentration is controlled to fluctuate within the range of 4.0-4.5 g / L by fine-tuning the flow rate of the precipitant and the complexing agent, and the nickel-cobalt-manganese hydroxide seed crystals of step 2 are continuously added to maintain the stable particle size. After the reaction is stable, the material is prepared to obtain nickel-cobalt-manganese hydroxide.

[0117] Step 4: The reaction product of step 3 is centrifuged and washed, and then dried and sieved to obtain a nickel-cobalt-manganese ternary precursor powder sample 2.

[0118] The SEM, CP and XRD images of the precursor are shown in Figure 3 , Figure 4 and Figure 5 shown.

[0119] Example 3

[0120] This embodiment provides a high-capacity cathode material precursor, and the preparation method thereof is as follows:

[0121] Step 1: Select soluble salts of nickel, cobalt and manganese as raw materials, prepare a 2.0 mol / L nickel-cobalt-manganese mixed solution according to the molar ratio of Ni:Co:Mn=90:9:1, prepare a 32 wt% NaOH aqueous solution, and prepare a 21 wt% ammonia aqueous solution as a complexing agent.

[0122] Step 2: Add a certain amount of pure water, NaOH aqueous solution and ammonia water into the reaction kettle and stir evenly to obtain a first base liquid with a pH of 11.00-11.60;

[0123] Step 3: Under stirring, constant temperature of 65° C. and nitrogen protection, a metal salt solution, a NaOH aqueous solution and an ammonia solution are introduced into a reactor containing the first bottom liquid, wherein the flow rate of the NaOH aqueous solution is always 0.37 times the flow rate of the nickel-cobalt-manganese mixed solution. Based on the total capacity of the reactor, the flow rate of the nickel-cobalt-manganese mixed solution is gradually increased from 2% / h to 12% / h; during the reaction process, the mother liquor is discharged through a concentration device, and the discharge rate is consistent with the total feed amount;

[0124] Step 4: post-treatment; after a certain reaction time, the particle size reaches a specified range, the reaction product of step 3 is centrifuged and washed, and then dried and sieved to obtain a nickel-cobalt-manganese ternary precursor powder sample 3.

[0125] During the reaction, the pH was adjusted to 11.40-11.60 within 3 hours of feeding by fine-tuning the flow rate of NaOH aqueous solution and ammonia water, and the ammonia concentration fluctuated within the range of 3-4.5 g / L to obtain a hydroxide reaction precipitate slurry. The reaction precipitate slurry was washed, centrifuged, dried, and sieved for demagnetization.

[0126] The SEM and XRD patterns of the precursor are shown in Figure 6 and Figure 7 shown.

[0127] Example 4

[0128] This embodiment provides a high-capacity cathode material precursor, and the preparation method thereof is as follows:

[0129] Step 1: Select soluble salts of nickel, cobalt and manganese as raw materials, prepare a 2.0 mol / L nickel-cobalt-manganese mixed solution according to the molar ratio of Ni:Co:Mn=94:5:1, prepare a 32 wt% NaOH aqueous solution, and prepare a 21 wt% ammonia aqueous solution as a complexing agent.

[0130] Step 2: adding a certain amount of pure water, the prepared NaOH aqueous solution and ammonia aqueous solution into a reactor, stirring evenly to obtain a first bottom liquid with a pH of 11.00-11.60; passing an inert gas to protect the first bottom liquid, and uniformly adding the nickel-cobalt-manganese mixed solution, the NaOH aqueous solution and the ammonia aqueous solution into the first bottom liquid reactor with a circulating magnetic pump, maintaining the temperature in the reactor constant, and continuously feeding and discharging. During the reaction, the pH is controlled to fluctuate within the range of 11.50-11.70 and the ammonia concentration is controlled to fluctuate within the range of 2.0-2.5 g / L by fine-tuning the flow rate of the precipitant and the complexing agent, so as to maintain the particle size stable. After the reaction is stable, the material is ready to be connected, and the slurry is centrifuged to obtain nickel-cobalt-manganese hydroxide seed crystals with an average particle size D50 of 2.5 μm.

[0131] Step 3: putting the nickel-cobalt-manganese hydroxide seed crystals of step 2 into a reactor, adding a certain amount of pure water, the prepared NaOH aqueous solution and ammonia aqueous solution into the reactor, stirring evenly, and obtaining a second bottom liquid with a pH of 10.40-10.60; passing an inert gas to the second bottom liquid for protection, and uniformly adding the nickel-cobalt-manganese mixed solution, the NaOH aqueous solution and the ammonia aqueous solution into the second bottom liquid reactor by a circulating magnetic pump, wherein the flow rate of the NaOH aqueous solution is 6.66% / h and the flow rate of the nickel-cobalt-manganese mixed solution is 18% / h based on the total capacity of the reactor, maintaining a constant temperature in the reactor, coprecipitating to generate a precursor, continuously feeding and discharging, and during the reaction process, controlling the pH to fluctuate within the range of 10.40-10.50 and the ammonia concentration to fluctuate within the range of 3.0-3.5 g / L by fine-tuning the flow rate of the precipitant and the complexing agent, and continuously adding the nickel-cobalt-manganese hydroxide seed crystals of step 2 to maintain a stable particle size, and preparing to receive the material after the reaction is stable to obtain nickel-cobalt-manganese hydroxide.

[0132] Step 4: The reaction product of step 3 is centrifuged and washed, and then dried and sieved to obtain a nickel-cobalt-manganese ternary precursor powder sample 4.

[0133] The SEM and XRD patterns of the precursor are shown in Figure 8 and Fig. 9 shown.

[0134] Example 5

[0135] This embodiment provides a high-capacity cathode material precursor, and the preparation method thereof is as follows:

[0136] Step 1: Select soluble salts of nickel, cobalt and manganese as raw materials, prepare a 2.0 mol / L nickel-cobalt-manganese mixed solution according to the molar ratio of Ni:Co:Mn=95:4:1, prepare a 32 wt% NaOH aqueous solution, and prepare a 21 wt% ammonia aqueous solution as a complexing agent.

[0137] Step 2: adding a certain amount of pure water, the prepared NaOH aqueous solution and ammonia aqueous solution into a reactor, stirring evenly to obtain a first bottom liquid with a pH of 11.00-11.60; passing an inert gas to protect the first bottom liquid, and uniformly adding the nickel-cobalt-manganese mixed solution, the NaOH aqueous solution and the ammonia aqueous solution into the first bottom liquid reactor with a circulating magnetic pump, maintaining the temperature in the reactor constant, and continuously feeding and discharging. During the reaction, the pH is controlled to fluctuate within the range of 11.50-11.70 and the ammonia concentration is controlled to fluctuate within the range of 4.0-4.5 g / L by fine-tuning the flow rate of the precipitant and the complexing agent, so as to maintain the particle size stable. After the reaction is stable, the material is ready to be connected, and the slurry is centrifuged to obtain nickel-cobalt-manganese hydroxide seed crystals with an average particle size D50 of 2.5 μm.

[0138] Step 3: putting the nickel-cobalt-manganese hydroxide seed crystals of step 2 into a reactor, adding a certain amount of pure water, the prepared NaOH aqueous solution (concentration 32wt%), and ammonia solution into the reactor, stirring evenly, and obtaining a second bottom liquid with a pH of 10.50-10.80; passing an inert gas to the second bottom liquid for protection, and uniformly adding the nickel-cobalt-manganese mixed solution, the NaOH aqueous solution, and the ammonia aqueous solution into the second bottom liquid reactor by a circulating magnetic pump, with the total capacity of the reactor being calculated at a flow rate of 5.92% / h for the liquid alkali, and a flow rate of 16% / h for the nickel-cobalt-manganese mixed solution, maintaining a constant temperature in the reactor, and continuously feeding and discharging the materials. During the reaction process, the pH is controlled to fluctuate within the range of 10.30-10.50 and the ammonia concentration is controlled to fluctuate within the range of 4.0-5.0g / L by fine-tuning the flow rates of the precipitant and the complexing agent, and the nickel-cobalt-manganese hydroxide seed crystals of step 2 are continuously added to maintain a stable particle size. After the reaction is stable, the materials are prepared to be connected to obtain nickel-cobalt-manganese hydroxide.

[0139] Step 4: The reaction product of step 3 is centrifuged and washed, and then dried and sieved to obtain a nickel-cobalt-manganese ternary precursor powder sample 5.

[0140] The SEM and XRD patterns of the precursor are shown in Fig.10 , Fig.11 shown.

[0141] Example 6

[0142] This embodiment provides a high-capacity cathode material precursor, and the preparation method thereof is as follows:

[0143] Step 1: Use soluble salts of nickel, cobalt and manganese as raw materials, prepare a 2.0 mol / L nickel-cobalt-manganese mixed solution according to the molar ratio of Ni:Co:Mn=93:6:1, prepare a 32wt% NaOH aqueous solution, prepare a 21wt% ammonia aqueous solution as a complexing agent, and prepare a sodium tungstate solution with a tungsten concentration of 0.88g / L.

[0144] Step 2: adding a certain amount of pure water, the prepared NaOH aqueous solution and ammonia aqueous solution into a reactor, stirring evenly to obtain a first bottom liquid with a pH of 11.30-11.60; passing an inert gas to protect the first bottom liquid, and using a circulating magnetic pump to uniformly add the prepared nickel-cobalt-manganese mixed solution, the NaOH aqueous solution and the ammonia aqueous solution into the first bottom liquid reactor, maintaining the temperature in the reactor constant, and continuously feeding and discharging. During the reaction, the pH is controlled to fluctuate within the range of 11.50-11.70 and the ammonia concentration is controlled to fluctuate within the range of 4.0-4.5 g / L by fine-tuning the flow rate of the precipitant and the complexing agent, so as to maintain the particle size stable. After the reaction is stable, the material is ready to be connected, and the slurry is centrifuged to obtain nickel-cobalt-manganese hydroxide seeds with an average particle size D50 of 2.5 μm.

[0145] Step 3: Put the nickel-cobalt-manganese hydroxide seed crystals prepared in step 2 into a reactor, add a certain amount of pure water, the above-prepared NaOH aqueous solution, and ammonia solution into the reactor, stir evenly, and obtain a second bottom liquid with a pH of 10.50-10.80; pass an inert gas to the second bottom liquid for protection, and use a circulating magnetic pump to uniformly add the nickel-cobalt-manganese mixed solution, NaOH aqueous solution, ammonia solution, and sodium tungstate solution into the second bottom liquid reactor. Based on the total capacity of the reactor, the flow rate of the NaOH aqueous solution is The flow rate of the 5.55% / h nickel-cobalt-manganese mixed solution is 15% / h, and the flow rate of the sodium tungstate solution is 7.5% / h. The temperature in the reactor is maintained constant, and the materials are continuously fed and discharged. During the reaction, the pH is controlled to be within the range of 10.10-10.20 and the ammonia concentration is controlled to fluctuate within the range of 3.5-4.5g / L by fine-tuning the flow rates of the precipitant and the complexing agent. The nickel-cobalt-manganese hydroxide seed crystals of step 2 are continuously added to maintain the stable particle size. After the reaction is stable, the material is prepared to be connected to obtain nickel-cobalt-manganese hydroxide.

[0146] Step 4: The reaction product of step 3 is centrifuged and washed, and then dried and sieved to obtain a nickel-cobalt-manganese ternary precursor powder sample 6.

[0147] The SEM and XRD patterns of the precursor are shown in Fig.12 , Fig.13 shown.

[0148] Comparative Example 1

[0149] This comparative example provides a positive electrode material precursor, and its preparation method is as follows:

[0150] Step 1: Select soluble salts of nickel, cobalt and manganese as raw materials, prepare a 2.0 mol / L nickel-cobalt-manganese mixed solution according to the molar ratio of Ni:Co:Mn=94:5:1, prepare a 32 wt% NaOH aqueous solution, and prepare a 21 wt% ammonia aqueous solution as a complexing agent.

[0151] Step 2: seed complex reaction; a certain amount of pure water, the above-prepared NaOH aqueous solution, and ammonia aqueous solution are added to the reactor, stirred evenly, and a first bottom liquid with a pH of 11.00-11.60 is obtained; an inert gas is passed through the first bottom liquid for protection, and a nickel-cobalt-manganese mixed solution, a NaOH aqueous solution, and an ammonia aqueous solution are uniformly added to the first bottom liquid reactor by a circulating magnetic pump, the temperature in the reactor is maintained constant, and the material is continuously fed and discharged. During the reaction, the pH is controlled to fluctuate within the range of 11.50-11.70 and the ammonia concentration is controlled to fluctuate within the range of 3.0-3.5 g / L by fine-tuning the flow rate of the precipitant and the complexing agent, so as to maintain the particle size stable. After the reaction is stable, the material is ready to be connected, and the slurry is centrifuged to obtain nickel-cobalt-manganese hydroxide seed crystals with an average particle size D50 of 2.5 μm.

[0152] Step 3: putting the nickel-cobalt-manganese hydroxide seed crystals of step 2 into a reactor, adding a certain amount of pure water, NaOH aqueous solution and ammonia solution into the reactor, stirring evenly, and obtaining a second bottom liquid with a pH of 10.50-10.80; passing an inert gas to the second bottom liquid for protection, and uniformly adding the nickel-cobalt-manganese mixed solution, the NaOH aqueous solution and the ammonia solution into the second bottom liquid reactor by a circulating magnetic pump, wherein the flow rate of the NaOH aqueous solution is 3.7% / h and the flow rate of the nickel-cobalt-manganese mixed solution is 10% / h based on the total capacity of the reactor, maintaining a constant temperature in the reactor, and continuously feeding and discharging the materials; during the reaction process, the pH is controlled to fluctuate within the range of 10.40-10.60 and the ammonia concentration is controlled to fluctuate within the range of 5.5-6.0 g / L by fine-tuning the flow rates of the NaOH aqueous solution and the ammonia solution, and the nickel-cobalt-manganese hydroxide seed crystals of step 2 are continuously added to maintain a stable particle size; after the reaction is stable, the materials are prepared to be connected to obtain nickel-cobalt-manganese hydroxide.

[0153] Step 4: The reaction product of step 3 is centrifuged and washed, and then dried and sieved to obtain a nickel-cobalt-manganese ternary precursor powder sample 7.

[0154] The SEM and XRD patterns of the precursor are shown in Fig.14 , Fig.15 shown.

[0155] Comparative Example 2

[0156] This comparative example provides a positive electrode material precursor, and its preparation method is as follows:

[0157] Step 1: Select soluble salts of nickel, cobalt and manganese as raw materials, prepare a 2.0 mol / L nickel-cobalt-manganese mixed solution according to the molar ratio of Ni:Co:Mn=90:9:1, prepare a 32 wt% NaOH aqueous solution, and prepare a 21 wt% ammonia aqueous solution as a complexing agent.

[0158] Step 2: Add a certain amount of pure water, the prepared NaOH aqueous solution and ammonia aqueous solution into the reaction kettle, stir evenly, and obtain a first base liquid with a pH of 11.00-11.60;

[0159] Step 3: material preparation; under stirring, constant temperature of 65°C and nitrogen protection, the metal salt solution, the prepared NaOH aqueous solution and the ammonia aqueous solution are introduced into the reactor containing the first bottom liquid; the flow rate of the NaOH aqueous solution is always 0.37 times the flow rate of the nickel-cobalt-manganese mixed solution, and the flow rate of the nickel-cobalt-manganese mixed solution is gradually increased from 2% / h to 15% / h based on the total capacity of the reactor; during the reaction, the mother liquor is discharged through the concentration equipment, and the discharge rate is consistent with the total feed amount;

[0160] Step 4: After a certain reaction time, the particle size reaches a specified range, and the reaction product of step 3 is centrifuged and washed, and then dried and sieved to obtain a nickel-cobalt-manganese ternary precursor powder sample 8.

[0161] During the reaction, the pH is adjusted to 11.60-12.00 within 3 hours of feeding by fine-tuning the flow rate of NaOH aqueous solution and ammonia water, and the ammonia concentration fluctuates within the range of 4.0-5.5 g / L to obtain a hydroxide reaction precipitate slurry. The reaction precipitate slurry is washed, centrifuged, dried, and sieved for demagnetization.

[0162] The SEM and XRD patterns of the precursor are shown in Fig.16 , Fig.17 shown.

[0163] The physical and chemical data of the precursors and the primary particle data obtained in Examples 1-6 and Comparative Examples 1-2 are shown in Table 1.

[0164] Table 1 Precursor physicochemical data and primary particle related data

[0165]

[0166] The positive electrode material precursor samples prepared in Example 1-6 and Comparative Example 1-2 were uniformly mixed with lithium hydroxide in a molar ratio of 1.05:1, and sintered in a box furnace under air atmosphere at a sintering temperature of 730° C. for 10 h. After cooling to room temperature, they were crushed and sieved to obtain the corresponding positive electrode materials.

[0167] The electrochemical performance test was conducted using a button-type semi-battery: the above-mentioned positive electrode materials were mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 8:1:1 to form a slurry, which was then coated on aluminum foil to form a positive electrode sheet. The negative electrode sheet used a metal lithium sheet, and the electrolyte used 1 mol / L LiPF6 / EC:DMC (volume ratio 1:1). The battery case, positive and negative electrode sheets, diaphragms, shrapnel, and gaskets were assembled into a button-type battery in a vacuum glove box. The electrochemical performance test was conducted using a blue electric test system. At room temperature, a 0.1C charge and discharge test was conducted at 3.0-4.3V.

[0168] The electrochemical performance data of the batteries prepared from the corresponding positive electrode materials of the precursors obtained in Examples 1-6 and Comparative Examples 1-2 are shown in Table 2; the (101) wafer numbers of Examples 1-6 and Comparative Examples 1-2 are obtained by the data in the XRD diagram and formulas (1) to (3), and the data are shown in Table 2:

[0169] Table 2 Precursor (101) wafer number and battery electrochemical performance data

[0170]

[0171] It can be seen from Tables 1-2 above and the SEM images of the positive electrode material precursors that the precursors obtained in Examples 1-6 of the present application have a number of (101) wafers within a suitable range, and the nickel content is relatively high (above 0.9). The 0.1C first discharge capacity of the lithium battery prepared from the corresponding positive electrode material is higher than that of Comparative Example 1-2, reaching more than 226mAh / g. The number of (101) wafers of the precursor material prepared in Comparative Example 1-2 is relatively high, and the average length and width of the primary particles and the aspect ratio are not within a suitable range, and the capacity of the battery prepared from its positive electrode material is also relatively low. The relevant physical and chemical performance parameters of Example 3 and Comparative Example 2 are similar. The number of (101) wafers in Comparative Example 2 is too high, resulting in a longer lithium ion transmission path and a slower deintercalation speed, which is not conducive to the material capacity. Since Example 3 has a smaller number of (101) wafers, its 0.1C first discharge capacity is also higher than that of Comparative Example 2. In addition, the primary particles of the precursors of Examples 1-6 are spindle-shaped, with an average width, average length and average aspect ratio within a suitable range, which can shorten the transmission path of lithium ions; the outer primary particles of the secondary particles of the positive electrode material precursor of Example 2 are radially arranged, and the overall porosity is 8.3%, which further improves the mobility of lithium ions, increases the contact area between lithium ions and the electrolyte, and improves the capacity of the lithium battery prepared with the corresponding positive electrode material.

[0172] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0173] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A high-capacity cathode material precursor, comprising secondary particles formed by a plurality of primary particles, characterized in that: The number N of (101) crystals of the positive electrode material precursor satisfies: 45≤N≤80; wherein N=D / d, D is the grain size of the (101) crystal plane, and d is the (101) crystal plane spacing; Preferably, the number N of (101) wafers of the positive electrode material precursor satisfies: 50≤N≤75.

2. The high-capacity cathode material precursor according to claim 1, characterized in that: The average particle size D50 of the positive electrode material precursor is 1-15 μm, and the particle size distribution span is 0.5<span<1.

7.

3. The high-capacity cathode material precursor according to claim 1, characterized in that: The positive electrode material precursor includes a plurality of spindle-shaped primary particles, and the positive electrode material precursor satisfies one or more of the following conditions: a. The average width of the primary particles is 30-120nm and the average length is 200-1200nm; b. The average aspect ratio of the primary particles is 4-25, preferably 4-15.

4. The high-capacity cathode material precursor according to claim 1, characterized in that: The primary particles located on the outer layer of the secondary particles of the positive electrode material precursor are arranged radially.

5. The high-capacity cathode material precursor according to any one of claims 1 to 4, characterized in that: The positive electrode material precursor meets one or more of the following conditions: A. The chemical formula of the positive electrode material precursor is Ni x Co y Mn z M w (OH)2, wherein x+y+z+w=1, 0.5≤x<1, 0≤y≤0.5, 0≤z≤0.5, 0≤w≤0.01, and M is selected from at least one of Ti, Mg, Zn, Cu, Al, Ga, In, F, La, Cr, Si, Sn, W, Mo, Y, Nb, Ca, Sm, V, Hf, Zr, Fe or B; Preferably, the chemical formula of the positive electrode material precursor is Ni x Co y Mn z M w (OH)2, wherein x+y+z+w=1, 0.9≤x<1, 0≤y≤0.1, 0≤z≤0.1, 0.001≤w≤0.01, M is Al or W; B. The average particle size D50 of the secondary particles of the positive electrode material precursor is 9-12 μm, and the particle size distribution span is 1≤span<1.5; C. The average particle size D50 of the secondary particles of the positive electrode material precursor is 1.5-5 μm, and the particle size distribution span is 0.5<span<1; D. The average particle size D50 of the secondary particles of the positive electrode material precursor is 9-12 μm, and the particle size distribution span is 0.5<span<1.

6. A method for preparing a high-capacity cathode material precursor, characterized in that: include: Under the protection of inert gas, a metal salt solution, a complexing agent and a precipitant are added to the base liquid to perform a coprecipitation reaction to obtain the high-capacity positive electrode material precursor; during the coprecipitation reaction, part of the liquid in the reaction system is continuously discharged or the solid-liquid mixed slurry is continuously discharged by overflow.

7. The preparation method according to claim 6, characterized in that: One or more of the following conditions are met: a. The concentration of the metal salt solution is 1.0-2.0 mol / L, and the solute in the metal salt solution is one or more of soluble nitrates, chlorides and sulfates of metals; b. The pH of the base solution is 9.5-12.0; c. The coprecipitation reaction process is controlled as follows: the temperature is 40-80°C, the pH is 9.5-11.7, and the ammonia concentration is 1-5g / L; d. The coprecipitation reaction further comprises stirring, and the stirring speed is 100-200r / min; e. the precipitating agent comprises an aqueous solution of sodium hydroxide, and the complexing agent comprises aqueous ammonia; f. During the coprecipitation reaction, the flow rate of the precipitant is 0.74-9.25% / h of the available volume of the reaction vessel, and the flow rate of the metal salt solution is 2-25% / h of the available volume of the reaction vessel; g. After the coprecipitation reaction is completed, the steps include solid-liquid separation, solid drying and screening.

8. A positive electrode material for a lithium ion battery, characterized in that: The raw material of the lithium-ion battery positive electrode material includes the high-capacity positive electrode material precursor as described in any one of claims 1-5.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery positive electrode material as claimed in claim 8.

10. A lithium battery device, characterized in that: The lithium-ion battery device comprises the lithium-ion battery as claimed in claim 9.

Citation Information

Cited By

  • Ultrahigh-nickel ternary precursor and preparation method thereof, positive electrode material, lithium ion battery and electric equipment

    CN120483291A

  • An ultrahigh-nickel ternary precursor, a preparation method thereof, a positive electrode material, a lithium ion battery, and an electric device

    CN120483291B